Legal Issues in Cases of Land Disputes Without Certificates (Study of Decision No. 18/Pdt/2022/Ptptk Juncto No. 30/Pdt.G/2021/PnKtp) - Aisyah Ayu Maharani (Faculty of Law, Universitas Negeri Semarang, 2025)
Land disputes, especially related to uncertified cultivated land, are still a complex problem in Indonesia. Case Decision Number 18/Pdt/2022/Ptptk juncto Number 30/Pdt.G/2021/PnKtp describes a situation where physical control of land without a certificate is legally disputed by another party claiming ownership rights. This study examines the legal issues in the dispute, considers the judge's decision, and examines the legal protection provided to the parties. The normative legal method with case studies was used to analyze the court decision. The results show that a land certificate is the strongest evidence of ownership, but continuous and open physical control can be the basis for a claim under certain conditions. However, without a certificate, the legal position of the cultivator becomes weak when faced with formal evidence from another party. The judge's consideration is very important in assessing evidence, good faith, and the history of land control. This decision reflects an effort to balance legal certainty, justice, and protection for all parties to the dispute.